Correction: Optically transparent high temperature shape memory polymers. Issue 26 (21st June 2016) - Xiao, Xinli; Qiu, Xueying; Kong, Deyan; Zhang, Wenbo; Liu, Yanju; Leng, Jinsong
Abstract : Correction for 'Optically transparent high temperature shape memory polymers' by Xinli Xiao et al., Soft Matter, 2016, 12, 2894–2900.